Analisis Pengaruh Waktu Belajar terhadap Nilai Ujian Mahasiswa - Fairuz Azzaria Siregar; Nayla Assyifa Cecilia; Mhd. Akbar Bathnul Wadi Nst; Adam Haris; Adelyna Oktavia Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to examine how study time affects test scores. A total of 64 students from various colleges and majors were given questionnaires to complete in order to collect data using a quantitative approach. The relationship between study time and exam scores was investigated using linear regression analysis. The findings show that study time and exam scores are significantly positively correlated, with students who spend more time studying often earning higher grades. The results of this study provide valuable information for teachers and students to create successful teaching and learning techniques. It is hoped that this study will form the basis for future research into the variables that influence academic success.